Comparison between the chemical composition of essential oils isolated from biocultivated Salvia rosmarinus Spenn. (Rosmarinus officinalis L.) and some commercial products - Stanislava Ivanova; Vanya Nalbantova; Niko Benbassat; Velina Dzhoglova; Zoya Dzhakova; Nina Koleva; Veselin Vasilev; Daniela Grekova-Kafalova; Kalin Ivanov (Pharmacia)
Salvia rosmarinus Spenn. (Rosmarinus officinalis L.) is an aromatic medicinal plant associated with rich phytochemical composition and significant pharmacological potential. The aim of the current study was to evaluate the chemical profile of eight samples containing essential oil (EO) from biocultivated Rosmarinus officinalis L. from different locations and various harvesting periods. Another key point of this study was the evaluation of the chemical profile of commercial products containing EO isolated from bio Salvia rosmarinus Spenn. It was observed that the harvest period may not have a significant effect on some of the bioactive components that are present but may affect their percentage content. Furthermore, not only the time of harvesting the plant material influences essential oil component composition, but also its location may have an effect.